Highly uniform InGaAs/InP quantum well nanowire array-based light emitting diodes. (May 2020) - Yang, Inseok; Kim, Sejeong; Niihori, Marika; Alabadla, Ahmed; Li, Ziyuan; Li, Li; Lockrey, Mark N.; Choi, Duk-Yong; Aharonovich, Igor; Wong-Leung, Jennifer; Tan, Hark Hoe; Jagadish, Chennupati; et al.
Abstract: III-V semiconductor nanowire infrared light emitting diodes (LEDs) have great potential for the development of Si-based integrated photonics. In this paper, we report the growth of highly uniform triangular prism InGaAs/InP single quantum well (QW) nanowires using a 2-step growth by metal organic chemical vapour deposition by selective area epitaxy technique. Based on these nanowire arrays, we demonstrate nanowire array LEDs with strong electroluminescence at two main peaks, originating from the axial and radial QW respectively and control the relative emission of those two peaks. We further reveal that a long lateral contact of the nanowire LED results in more intense radial QW emission by shortening the current path to the radial quantum well. Our study provides an important foundation for the development of high-performance array nanowire-based devices such as high-power multi-wavelength LEDs, high power electrically switchable wavelength-selectors and QW infrared photodetectors. Graphical abstract: Image 1 Highlights: Demonstration of highly uniform triangular prism InGaAs/InP quantum well nanowires. Multi-wavelength emission from the prism InGaAs/InP quantum well nanowires. Modification of electroluminescence spectra by the side contact coverage. Minimisation of optical loss through the substrate by simple fabrication processes.